Uterovesical Abscess as Late Cesarean Complication - a Case Report and Review of the Literature - Oana Mihaela TEODOR; Delia Maria GRADINARU-FOMETESCU; Ovidiu BRATU; Florin Costel DOBRITOIU; Andreea Nicoleta MARINESCU; Monica Mihaela CIRSTOIU (Modern Medicine)
Pelvic abscesses located in the uterovesical space usually appear postpartum after cesarean delivery. Late presentation after months or years following surgery is rarely reported, especially in immunocompetent patients. We report the case of a young patient presenting an abscess of the uterovesical pouch, infiltrated in the myometrium, posterior wall of the bladder and parametrium. The case particularities include limited identifiable predisposing risk factors, acute onset of symptoms and belated diagnosis eight years after her second cesarean. The abscess removal by laparotomy required extensive debridement, total hysterectomy, bilateral salpingectomy and partial cystectomy, with good outcome after surgical treatment. We highlight the importance of a mixt urogynecology team for individualized case management and we discuss similitudes with other late cesarean complications.